BIJIH BESI DI DAERAH BONTOCANI KABUPATEN BONE SULAWESI-SELATAN - Utoyo, Harry (Pusat Survei Geologi, 2008)
The iron ore located at Bontocani, Bone Regency, South Sulawesi is found in the form of boulders. The iron ore is associated with intrusions of granodiorite, pegmatite granodiorite and quartz as a result of moving up magmatic liquid containing iron ore, then it is enriched by the magmatic liquid remains that form granodiorite known as hydrothermal liquid through the cracks. Sometimes, the iron ore is an aggregate at the contact zone between granodiorite intrusive and limestone. Mineral association occurred among garnet, quartz and ore mineral of magnetite and hematite, then mineralization in the research area is assumed as skarn type.Prospective area located at Tanjung village, in the south part of research area is 187.5 ha accompanied by magnetite mineralization and the degree of Fetotal = 61,98 %, and at Pake village (220.78 ha) located at the north part and dominated by hematite mineralization with Fetotal = 52,35 %. Keywords: iron ore prospecting, granodiorite, pegmatite granodiorite, prospective area